Kultūros paveldo ir lituanistinių mokslo duomenų skaitmeninimas Lietuvoje: 2011 metų situacija* - Laužikas, Rimvydas; Vosyliūtė, Ingrida (Information & Media, 2012)
Straipsnyje susipažindinama su 2011 m. atlikto paveldo ir lituanistinių mokslo duomenų skaitmeninimo situacijos Lietuvoje tyrimo svarbiausiais rezultatais: apžvelgiamos, palyginamos esamos sistemos ir skaitmeninančos institucijos; aptariami skaitmeninimą lemiantys aplinkos veiksniai, ištekliai. Straipsnio pabaigoje pateikiamos svarbiausios esamos problemos, diskutuojami jų sprendimo būdai. Tyrimą atliko Vilniaus universiteto Komunikacijos fakultetas, kartu su UAB „IO Projects“ vykdydamas Lietuvos mokslo tarybos finansuojamą projektą „Lituanistinių mokslo tyrimų ir paveldo infrastruktūrų tinklo kūrimas: projektavimo fazė“.Reikšminiai žodžiai: paveldas, lituanistiniai mokslo duomenys, skaitmeninimas Lietuvoje.Digitization of cultural heritage and scientific data of Lithuanian studies in Lithuania: the 2011 situationRimvydas Laužikas, Ingrida Vosyliūtė SummaryThe article presents the main data on the situation with the digitization of heritage and Lithuanian studies scientific data in Lithuania in 2011. The study was carried out at the Faculty of Communication of Vilnius University when implementing the project Development of the National Network of Infrastructure of Lithuanian Studies Scientific Research and Heritage: the Design Phase financed by the Research Council of Lithuania.The digitization of cultural heritage and Lithuanian studies scientific data has been going on in Lithuania for already more than 15 years. During that time, near 100 different information infrastructures have been developed. Most of scientific data are digitized by the Institute of the Lithuanian Language, Institute of Lithuanian Literature and Folklore, Vilnius University, Vytautas Magnus University and Kaunas University of Technology. From the quantitative point of view, the number of IS controlled by a memory institution is less, but this is determined by a higher concentration and level of strategic management in this sector, which is supervised by the Ministry of Culture.The environmental analysis has shown that the strategic priority given to the scientific research of Lithuanian studies, digitization of their scientific data, heritage data and the legal, political, financial, technological, institutional environment in Lithuania are favourable. There is no factor or reason to be singled out for its strongest influence on the development of infrastructures in Lithuania, because their development is determined by the totality of interrelated factors. When assessing systematically, it was established that the creation and development of the network of Lithuanian studies infrastructure would be most greatly influenced by institutional, technological and function distribution factors; legal and administrative factors would influence them less, while the influence of economic and social factors would be the least.An important source of problems in the digitization of heritage and scientific data of Lithuanian studies in Lithuania is the fact that these sciences, scientific institutions and their infrastructures are supervised by the Ministry of Culture and Science, whereas the memory institutions and information infrastructures of the most important sources (heritage) are in the competence of the Ministry of Culture. Therefore, the creation of specialized information systems and databases in research and memory institutions is almost non-coordinated, and the interoperability of created infrastructures is not ensured.In the existing infrastructures of Lithuanian studies scientific research and heritage, the accumulated digital and digitized content has a great social and cultural significance, but it could be accessed and used much more efficiently upon merging the resources stored in different infrastructures into one single network and upon implementing the strategic management tools in the sphere of digitization of scientific data and creation of research infrastructures.Based on the study results, the following prospects for infrastructure development should be singled out: the further development of the created infrastructures in the technological sense as well as in the sense of contents; creation of inter-institutional infrastructures by optimising the resources and avoiding the duplication of activities; promotion of cooperation and networking by decreasing decentralization and the use of general standards. 10.5pt; line-height: 115%; font-family: Calibri, sans-serif;">